Narrativas sobre la situación emocional en las personas mayores de 60 años que pertenecen a la Unidad Social en Choachí- Cundinamarca (2023)
The objective of this study is to describe the narratives about the emotional situation in people over 60 years of age who belong to the Unidad Social San Luis María de Montfort shelter in Choachí-Cundinamarca. In this order of ideas, the study methodology is based on qualitative research, based on a phenomenological paradigm and a specific data collection technique, the semi-structured interview. To carry out the interview, the participation of seven people over the age of sixty belonging to the institution was requested. At the end of this stage, the narratives that allowed establishing the results were analyzed through the qualitative data software "ATLAS.ti".